Ergonomics in food production: Improving workstations to reduce disergonomic risks - Echevarria Caicedo, Victoria Jacqueline; Sánchez Pérez, Joselito; Arroyo Ulloa, Maximiliano (LACCEI, 2025)
In this research, the workstations in the production area of a food company were improved to reduce ergonomic risks. The methodology began with a Rapid Ergonomic Risk Assessment to classify risk levels as acceptable (green) or high (red). Based on these results, ergonomic evaluation methods REBA and NIOSH were applied. REBA identified six workstations with medium risk, requiring intervention, while NIOSH revealed that the maximum allowable weight to be lifted by operators was 10,138 kg. The implemented improvements included the installation of five conveyor belts to eliminate the position of sack loaders, optimization of lighting using the quadrant method, and ergonomic training for workers. After these modifications, risks were reassessed, and a cost-benefit analysis of the redesign was conducted. As a result, a 100% reduction in risks related to static postures and manual load handling was achieved, avoiding SUNAFIL fines of S/ 27 140 and other costs amounting to S/ 87 420. The investment, recovered within 1 year and 9 months, generated a net profit of S/ 83 603, a Net Present Value (NPV) of S/ 191 537, an Internal Rate of Return (IRR) of 27%, and a Benefit/Cost (B/C) ratio of 1,71, demonstrating that the investment was highly profitable and viable, with a rapid recovery of the capital invested.